1999
DOI: 10.1021/jp984271w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Aqueous Solvation Free Energies from Properties of Solute Molecular Surface Electrostatic Potentials

Abstract: It is shown that aqueous solvation free energies, ∆G sol , can be expressed quantitatively in terms of properties of the molecular surface electrostatic potentials of the solutes. The latter are obtained computationally by the B3P86/6-31+G** density functional procedure. Regression analyses and an experimental database encompassing 50 solutes of various types are used to obtain an analytical representation of ∆G sol which reproduces the experimental values with a standard deviation of 1.57 kJ/mol and an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…Many macroscopic properties of bulk energetic materials can be determined from quantum mechanical information calculated for isolated molecules. Politzer and coworkers [24][25][26][27][28][29][30][31][32] have established the quantum mechanical electrostatic calculations of the isolated molecule to determine aqueous solvation free energies, lattice energies in ionic crystals, diffusion coefficients, solubilities, boiling points, partition coefficients, critical constants and impact sensitivities. Rice and coworkers [21,33] utilized these ideas to predict heats of formation of energetic materials in the gas, liquid and solid state as well as heats of detonation from quantum mechanical computation of isolated molecule.…”
Section: Group Additivity and Quantum Mechanical Methodsmentioning
confidence: 99%
“…Many macroscopic properties of bulk energetic materials can be determined from quantum mechanical information calculated for isolated molecules. Politzer and coworkers [24][25][26][27][28][29][30][31][32] have established the quantum mechanical electrostatic calculations of the isolated molecule to determine aqueous solvation free energies, lattice energies in ionic crystals, diffusion coefficients, solubilities, boiling points, partition coefficients, critical constants and impact sensitivities. Rice and coworkers [21,33] utilized these ideas to predict heats of formation of energetic materials in the gas, liquid and solid state as well as heats of detonation from quantum mechanical computation of isolated molecule.…”
Section: Group Additivity and Quantum Mechanical Methodsmentioning
confidence: 99%
“…Using a GIPF expression developed earlier [70], we calculated the free energies of solvation of these nonionic and zwitterionic tautomers. Our results, when combined with the computed differences in energy between the two forms, were in very satisfactory agreement with the available experimental data and confirmed that all three molecules are zwitterions in aqueous solution.…”
Section: Zwitterionsmentioning
confidence: 99%
“…In both cases, the condensed system is represented by an assembly of interacting particles: the statistical distribution of any property, or its evolution in time, is obtained as a sum over all particles with appropriate rules. These techniques have been used by Duffy and Jorgensen 20 and by Murray and co-workers 21 to correlate the ∆ solv G°of different solutes in water to MC simulation-derived and molecular electrostatic potential (MEP)-derived descriptors.…”
Section: Prediction Of the Solvation Free Energymentioning
confidence: 99%